Peran Komunikasi dan Agreeableness Terhadap Co-Parenting pada Pasangan Beda Etnis - Liu, Berliana Nurannisa Kusuma; Setiawan, Jenny Lukito (Universitas Ciputra Surabaya, 2020)
This study aims to see the role of communication and agreeableness towards co-parenting in mixed couple. There are 3 hypothesis presented in this study to see the role of communication and agreeableness towards co-parenting in mixed couple. The result of this study is that communication and agreeableness contributed significantly towards co-parenting in mixed couple. This study was conducted on 41 mixed couple or 82 people in total. This study use quantitive method with correlational design. The result of multiple regression test showed that communication and agreeableness contributed significantly to co-parenting (F= 28,664; p < 0,05). The result of multiple regression also showed that communication and agreeableness contributed respectively to co-parenting. Communication contributed higher than agreeableness, and that is 38,7% (R2= 0,387; p < 0,05). While agreeableness contributed 3,4% (R2= 0,034; p < 0,05).